Effects of the STM tip on atomic positions: an explanation for the non-observation of adsorbed molecules? - Ramos, Marta M. D. (1990)
We have performed self-consistent calculations for molecules adsorbed on a metal substrate in the presence of a scanning tunnelling microscope (STM) tip. These calculations of comprise (i) estimates of the inhomogeneous electric field, (ii) the self-consistent calculation of both electronic structure and molecular geometry using an extended semi-empirical molecular orbital method, and (iii) estimates of the tunnelling current using the resulting wave-functions and geometries. The STM tip causes changes in atomic positions which can complicate the link between current and geometry. In particular, induced molecular reorientation may well explain the lack of observation by STM of adsorbed CO on metals.